2014
DOI: 10.1097/mcg.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis Regression in Patients With Viral Hepatitis B and C

Abstract: The results of our review suggest that viral suppression in CHB and sustained virologic response in CHC can be associated with histologic regression of cirrhosis in select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 75 publications
0
30
0
1
Order By: Relevance
“…It is based primarily on the work of Ian Wanless and colleagues in which the regression of cirrhosis was highlighted, first in treated chronic hepatitis B and then in other studies and in other diseases [7]. While the possibility that cirrhosis could regress to livers with improved or even normal functioning status was highly controversial when Wanless first presented the concept [7][8][9][10], subsequent reports, particularly in patients with hepatitis C cirrhosis in which sustained viral response was obtained by interferonbased therapies, confirmed that this actually happens [3][4][5].…”
Section: P-i-r Scorementioning
confidence: 99%
See 1 more Smart Citation
“…It is based primarily on the work of Ian Wanless and colleagues in which the regression of cirrhosis was highlighted, first in treated chronic hepatitis B and then in other studies and in other diseases [7]. While the possibility that cirrhosis could regress to livers with improved or even normal functioning status was highly controversial when Wanless first presented the concept [7][8][9][10], subsequent reports, particularly in patients with hepatitis C cirrhosis in which sustained viral response was obtained by interferonbased therapies, confirmed that this actually happens [3][4][5].…”
Section: P-i-r Scorementioning
confidence: 99%
“…The potential for liver fibrosis to regress following successful treatment has been acknowledged for many years, particularly in the realm of viral hepatitis where successful suppression of hepatitis B virus (HBV) replication and eradication of hepatitis C virus (HCV) lead to regression of scar in most patients [1][2][3][4][5]. However, incorporation of such concepts into diagnosis and assessment of liver diseases in biopsies and resection specimens has not kept pace.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was considered to be a dynamic process depending on the balance between degradation and remodeling of extracellular matrix deposition by metalloproteinase enzymes and their tissue inhibitors, yet the mechanism is not completely understood. For instance, treating the cause of liver disease was thought to improve the ability of liver tissue to reverse fibrosis, but studies showed incomplete or insignificant improvement in some patients [6,7]. This means that, there are other co-factors which if treated could improve the healing response.…”
Section: Discussionmentioning
confidence: 99%
“…It was considered irreversible in the past but the current studies showed that fibrosis [4][5][6], and even cirrhosis [7,8] in some series, could be reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cirrhosis is the end-stage result of fibrosis in liver parenchyma and should be generally irreversible [3]. Liver fibrosis is characterized by excessive accumulation of extracellular matrix, with the formation of scar tissue encapsulating the area of injury [4].…”
Section: Introductionmentioning
confidence: 99%